Smart City as a Service (SCaaS): A Future Roadmap for E-Government Smart City Cloud Computing Initiatives - Clohessy, Trevor; Acton, Thomas; Morgan, Lorraine (Proceedings of the 2014 IEEE/ACM 7th International Conference on Utility and Cloud Computing, 2014)
The concept of a smart city has been identified as not only representing a crucible for technological innovation, a medium for realizing global integration but also as an exemplar response for addressing current and impending global issues (societal, environmental economic and governance). There is now general consensus that emerging information communication technologies (ICT) such as cloud computing can be deployed as a vehicle for catalyzing smart city innovation. There is also evidence to suggest that cloud computing has become a strategic direction for many e-government initiatives as evidenced by the emergence of global government clouds (G-Cloud). In this paper, we delineate the concept of a smart city and explore the propitious potential of cloud computing to enable the development of smart cities. We review the current state of the art pertaining to a selection of cloud schemes currently being operationalized by international governments aimed at capitalizing on the nascent innovation capabilities of the technological paradigm, and present a future research roadmap for cloud facilitated smart city development.